Determinants of Consumer Perceptions towards Value-added Millet Products in Kerala, India - Vattekkad, Reshma; Jatav, Surendra Singh; Kunchu, Pradeesh; Krishnankutty, Mohandas Vallamala; Krishnan, Manikandan (Indian Journal of Extension Education, 2025)
The paper examines determinants affecting the consumption of value-added millet products among consumers in Kerala, India. Using multi-stage sampling, 326 samples were collected from three districts of Kerala state in India, namely, Trivandrum, Palakkad, and Malappuram in December 2023. The study employed t-tests and one-way ANOVA to investigate the potential impact of socio-economic characteristics on consumer perception of value-added millet products. The structural equation model (SEM) was employed to analyse the determinants, like nutritional value, price, package quality, flavour, and media exposure, on consumer behaviour to buying millet products. Consumer perceptions vary according to demographic features such as gender, age, marital status, area of residence, and income. The SEM model states that all five determinants have a significant impact on the perception of consumers except price. With an unstandardized coefficient of 0.59, the "nutritional benefit" determinant had the strongest positive influence on consumer perception, while with an unstandardized coefficient of -0.023, price had a negative influence on the perception of consumers. The results imply that to increase the acceptance of value-added millet products, initiatives to promote millet consumption should concentrate on enhancing nutritional knowledge, taste, flavour, quality of production, and cost reduction.